Calcification of coronary arteries in patients with calcium pyrophosphate crystal deposition disease and knee osteoarthritis - M. S. Eliseev; D. S. Novikova; A. M. Novikova; L. M. Blank; O. V. Zhelyabina; M. V. Cherkasova; E. L. Nasonov (Научно-практическая ревматология, 2021)
The frequency of vascular calcification in patients with osteoarthritis (OA) and calcium pyrophosphate crystal deposition disease (CPPD) has not yet been studied, and the role of calcium crystals (basic and pyrophosphates) in the development of calcification is also unknown.Objective. Determine the presence and degree of calcification of the coronary vessels in patients with calcium pyrophosphate crystal deposition disease and osteoarthritis of the knee joints with no clinical signs of cardiovascular diseases.Materials and methods. One-stage, single-center study, performed by the “case – control” method. The main group – 20 patients with CPPD, the comparison group – 20 patients with OA of the knee joints. Inclusion criteria: age from 18 to 65 years; absence of clinical signs of cardiovascular disease at the time of examination and indications of a history of cardiovascular accidents. Exclusion criteria: unsigned informed consent; pregnancy; breastfeeding; other rheumatic disease; cancer; high and very high cardiovascular risk on the SCORE scale. The survey included an assessment of anthropometric data, blood pressure (BP), lipid profile, serum levels of glucose, creatinine, uric acid, C-reactive protein, vitamin D, osteoprotegerin, parathyroid hormone, and the levels of magnesium, phosphorus, and total calcium were studied. All patients underwent multispiral computed tomography with determination of calcium count and the number of affected arteries. To calculate the coronary score, the A.S. Agatston et al.Results and discussion. Most of the parameters in the compared groups did not differ. When assessing the calcification of the coronary arteries according to the A.S. Agatston et al. 9 (45%) patients with CPPD and 8 (40%) patients with OA had a coronary calcium score >1. Quantitative indicators of calcium score can correspond to coronary artery stenosis ≥20% in 8 (40%) patients with CPPD and in 5 (25%) patients with OA according to J.A. Rumberger et al. The serum level of osteoprotegerin was significantly higher in patients with a calcium score ≥27 according to J.A. Rumberger et al. (p=0.04). Calcification was detected in 9 (56%) of 16 patients with serum vitamin D levels <30 ng/ml and in 8 (33%) of 24 patients with serum vitamin D levels >30 ng/ml.Conclusions. In patients with an initially low cardiovascular risk, the probability of a combination of chondrocalcinosis and cardiovascular calcification is 45%, in OA it is 40%. The risk factors for coronary calcification in patients with CPPD and OA should be studied further.